FORMULATION DEVELOPMENT AND EVALUATION OF ALMOND GUM BASED SUSTAINED RELEASE MATRIX TABLET OF INDOMETHACIN - Sunayana S, Ruchi; Dv, Gowda; Gupta N, Vishal; Sivadasu, Praveen; M, Manjunath (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The aspiration of the current research involves employing various concentrations of polymer and filler to develop indomethacin sustained release (SR) matrix tablets. The objective of this research work is to reduce dosing frequency thereby increasing patients compliance and enhanced therapeutic activity. Methods: Polymers such as Almond gum (AG), polyvinylpyrrolidone (PVP), and starch at different concentrations were used for formulating SR polymeric matrix tablets. Evaluation of pre-compression and post-compression parameters was done for both granules and formulated tablets. Results: Results obtained from pre-compression parameters and post-compression parameters suggested that all the parameters are within the prescribed limits, demonstrating that formulated granules had shown better flow properties. The morphological characteristics of the developed tablet were observed by employing scanning electron microscope where the surface of the tablet was found to be smooth from the in vitro dissolution study, combination of AG (30 mg) with PVP (30 mg), and starch used as a filler has sustained the release of drug up to 10 h. Conclusion: Therefore, developed polymeric matrix tablet exhibited enhanced potency over a conventional tablet by exhibiting an excellent dissolution profile for a period of 10 h.